Detection of Aerosols in Antarctica From Long‐Range Transport of the 2009 Australian Wildfires. Issue 23 (4th December 2020) - Jumelet, J.; Klekociuk, A. R.; Alexander, S. P.; Bekki, S.; Hauchecorne, A.; Vernier, J. P.; Fromm, M.; Keckhut, P.
Abstract: We analyze the long‐range transport to high latitudes of a smoke particle filament originating from the extratropics plume after the Australian wildfires colloquially known as "Black Saturday" on 7 February and report the first Antarctic stratospheric lidar characterization of such aerosols. Using a high‐resolution transport/microphysical model, we show that the monitoring cloud/aerosol lidar instrument operating at the French Antarctic station Dumont d'Urville (DDU, 66°S to 140°E) recorded a signature of those aerosols. The 532 nm scattering ratio of this filament is comparable to typical moderate stratospheric volcanic plume, with values between 1.4 and 1.6 on the first and third days of March above DDU station at around the 14 and 16 km altitude, respectively. A dedicated model is described and its ability to track down fine optical signatures is validated against Antarctic lidar elastic aerosol and DIAL ozone measurements. Using 1 month of tropical Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) data to support a relatively simple microphysical scheme, we report modeled aerosol presence above DDU station after advection of the aerosol size distribution. In situ measurements also report associated positive ozone anomaly. This case study provides evidence that biomass burning events injecting significant amounts of material up to stratospheric altitudes can be transported toward high latitudes. We highlight a potential imprint of smoke particles on the Antarctic atmosphere over larger time scales. Any underestimation of the global impact of such deep particle transport will lead to uncertainties in modeling the associated chemical or radiative effects, especially in polar regions, where specific microphysical and chemical processes take place. Plain Language Summary: A series of bushfires ignited in the Australian state of Victoria on 7 February 2009 and ended up being the most devastating fire hazard in Australia before the recent 2019/2020 fires. Active remote sensing monitoring instruments are deployed on the French Antarctic station Dumont d'Urville. For the first time, the station recorded presence of aerosols having originated from this biomass burning event at stratospheric altitudes using the atmospheric laser sounding technique (lidar). We combine model calculations to space‐borne and ground‐based measurements to track the long‐range transport of a small filament of the aerosol plume down to the Antarctic station to highlight the possible global impact of such events. Key Points: In 2009, the DDU Antarctic Lidar reported an unusual backscatter ratio of 1.4 above 13 km, first signature of the Australian wildfires A microphysical transport model using CALIOP data as constraints successfully models the optical properties of the Antarctic lidar overpass Positive ozone anomaly is reported using lidar measurements